Synthesium pantoporiae and Synthesium tursionis (Digenea; Brachycladiidae Odhner, 1905) in Pontoporia blainvillei Gervais & d’Orbigny, 1844 (Cetacea, Pontoporiidae) in south of the state of Santa Catarina, Brazil - Marinho de Quadros, Rosiléia (2024)
Parasitic susceptibility can occur indidually or in populations due to several factors, such as: parasite species, abundance, host health status (age, nutritional status) and competition between diferente types of parasites. This study reports the presence of Synthesium pontoporiae Raga, Aznar, Balbuena & Dailey, 1994  and Synthesium tursionis (Marchi, 1873) in Pontoporia blainvillei Gervais & D’Orbigny, 1844 found dead on the beaches of the mucipalities of Laguna, Imbituba and Garopaba, located on the southern coast of Santa Catarina, Brazil, between 2017 until 2020. A total of 144 specimens of trematodes were identified in 14 evaluated animals, with a prevalence of 35,71%, mean abundance of 10.28 and mean intensity of infection of 28.80. The average intestinal lenght was 8.96 meters, ranging from 1.90 to 29.10 meters. The occurence of parasites can be indicative of the relationship between feeding habits and the dispersion of animals in the ocean and, in the case of the presence of the Synthesium trematode, this knowledge is fundamental in the research for more information about the evolutionary cycle of this parasite. In this study, although the beaches where the animals were found are geographically very close, there were significant diferences, mainly between the intensity and parasite abundance, which demonstrates the need for further studies to understand the relationship between the findings in this study with the diet and the presence of possible intermediate hosts of this parasite in these regions.